Model Multisensori: Solusi Stimulasi LiterasiAnak Prasekolah - Lisnawati Ruhaena (Jurnal Psikologi, 2015)
This research aimed to develop a model of literacy stimulation for preschool children in order to meet their needs and to overcome parents’ problems in stimulating literacy in their children at home. The data of children’s needs and parents’ problem were obtained from questionnaires and focus group discussion. The questionnaires were filled by 75 mothers whose children aged 3-5 years old in Surakarta. Then, 26 of them attended focused group discussion. The data obtained showed that there was a problem in these children’s early literacy development. Most of them were lack of interest in literacy activities and mostof the parents were unable to attract their children’s attention and interest. The problem faced by the parents was the lack of skill in selecting and doing literacy activities in accordance with their children’s needs. A multisensory model was designed to improve pre-school children’s interest in early development of literacy and to increase parents’ skill in stimulating their children’s interest.